Insulin Resistance, Metabolic Syndrome and Diabetes in Women at High Risk for Breast Cancer - Dumais, Valerie (Université d'Ottawa / University of Ottawa, 2014)
Purpose: The overall objective of this prospective study was to quantify the prevalence of insulin resistance (IR), metabolic syndrome (MetS) and type 2 diabetes (T2D) in women at high risk for breast cancer, stratified by menopausal status. We also aimed to calculate the sample size required for a future case-control study comparing these prevalences to those of the general population. Methods: Participants consisted of 100 Caucasian women above the age of 35 with an estimated 5yr risk of breast cancer ≥1.7%. A comprehensive metabolic profile was obtained for each participant based on a questionnaire, fasting blood sample and biophysical measurements. Results: In comparison to published prevalence’s of IR, MetS and T2D in the general population, the prevalence of IR and MetS is higher in our study sample. High risk postmenopausal women have a higher prevalence of body mass index, waist circumference, MetS and hypertension than premenopausal women. We have shown a significant correlation between Gail score and high-density lipoprotein cholesterol. Conclusions: The sample size calculation, based on the prevalence’s obtained in the present study, support the significance and feasibility of a future case control study comparing the prevalence of IR and MetS in women at high risk and average risk for breast cancer. Further studies are needed to clarify the underlying mechanisms for the association between IR, MetS, T2D and breast cancer risk.
Keywords: Diabetes; Insulin Resistance; Breast Cancer; Metabolic Syndrome; High Risk